Socially advantaged? How social affiliations influence access to valuable service professional transactions - Gubler, Timothy; Cooper, Ryan (Strategic Management Journal, 2019)
[Research summary:This article theorizes that social capital produced by social affiliations allows service professionals to gain access to higher-value transactions through increased reputation for trustworthiness, which then aids them in further building reputation and engaging in entrepreneurship. Using a unique approach that pairs Utah residential real estate data with church congregation boundaries, we find that affiliations enable real estate agents to list 14% more expensive homes, and to consequently build reputation useful for future nonaffiliated transactions. We observe large reputation-building benefits for early-career agents, particularly for agents in low-reputation firms. Strikingly, we find this lowers entrepreneurship entry by 6%. These results imply that social affiliations can substitute for reputation in selection, enabling professionals to build reputation, which then has important career implications. Managerial summary:This article explores how social relationships between real estate agents and home sellers influence the value of transactions agents engage in. Sellers increasingly trust agents with whom they share a social affiliation, which allows agents to better secure high-value listings and build reputation. This benefits agent in securing future valuable transactions with nonaffiliated clients. Using residential real estate data and geographically assigned church congregations, we find that agents list 14% more expensive homes when listing for affiliated clients, and that this builds agent reputation significantly faster than listing for nonaffiliated clients. Interestingly, we find listing for affiliated clients reduces future entrepreneurship 6%. Our study suggests that service professionals can leverage social affiliations to build reputation that helps them establish clientele and improve performance.]